Sosialisa Izin Air Bawah Tanah Dan Minuman Keras Kepada Pelaku Usaha - Ananda Putra, I Gusti Agung; I Gede Yoga Bayu Priatama (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
The socialization of permits to use underground water and liquor to business actors is an understanding or education for business actors to understand the impact and advantages of having this permit. Not only the impact, but there are violations that will be obtained if you violate the rules that have been provided for by regional regulations, one of the most fatal is the closure of a place of business. Therefore, the socialization of permits related to groundwater and liquor is a challenge that needs to be monitored so that business actors become more knowledgeable and understand regarding the socialization of permits for the use of underground water and liquor. Kata Kunci: Usage Permits, Challenges, Entrepreneurs